2022
DOI: 10.1166/jon.2022.1857
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Thermal Conductivity Enhancement in Carbon Nanofluids Caused by Surfactant High Concentration

Abstract: In this study, structural and thermal properties of dispersed carbon nanomaterials such as single-wall carbon nanotubes and graphene in water are investigated. Carbon nanostructures are dispersed in the fluid through surfactant and ultrasonication treatment. Structural studies of the samples are carried out by Raman spectroscopy which show that the dispersion process leads to the formation of two kind of nanofluids: nanostructured graphene based and single-wall carbon nanotubes ones. The first in the form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Methomyl (Goldben) is a systemic, anticholinesterase broad-spectrum carbamate insecticide and has widely been used against many insect pests. Chemical pesticides including Chlorfenapyr and Methomyl generally show rapid potency against many insect pests including lepidopterans (Darabian and Yarahmadi, 2017;Desaeger et al, 2011;Sallam et al, 2015). Likewise, in our study, both Chlorfenapyr and Methomyl appear to be highly effective against S. ocellatella, S. littoralis and S. exigua.…”
Section: Discussionmentioning
confidence: 99%
“…Methomyl (Goldben) is a systemic, anticholinesterase broad-spectrum carbamate insecticide and has widely been used against many insect pests. Chemical pesticides including Chlorfenapyr and Methomyl generally show rapid potency against many insect pests including lepidopterans (Darabian and Yarahmadi, 2017;Desaeger et al, 2011;Sallam et al, 2015). Likewise, in our study, both Chlorfenapyr and Methomyl appear to be highly effective against S. ocellatella, S. littoralis and S. exigua.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the unique properties of the nanofluid, the thermal conductivity of the fluid can either rise or decrease with increasing concentration. According to research by Borode et al, [35] and Darabian et al, [36], as concentration increases, a nanofluid's thermal conductivity decreases. On the other hand, additional research has demonstrated that as concentration increases, the nanofluids' thermal conductivity also can increase [37,38].…”
Section: Thermophysical Properties Of Nanofluids 331 Thermal Conducti...mentioning
confidence: 97%